2021
DOI: 10.1186/s13567-021-00953-7
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro models show unexpected degrees of virulence among Toxoplasma gondii type II and III isolates from sheep

Abstract: Toxoplasma gondii is an important zoonotic agent with high genetic diversity, complex epidemiology, and variable clinical outcomes in animals and humans. In veterinary medicine, this apicomplexan parasite is considered one of the main infectious agents responsible for reproductive failure in small ruminants worldwide. The aim of this study was to phenotypically characterize 10 Spanish T. gondii isolates recently obtained from sheep in a normalized mouse model and in an ovine trophoblast cell line (AH-1) as inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(53 citation statements)
references
References 62 publications
2
50
1
Order By: Relevance
“…In short, findings should be always interpreted cautiously, as well as with interest, since strains that circulate in wildlife are a source of infection for domestic animals and humans, and have been associated with greater pathogenicity at least in North and South America ( Dubey et al., 2014 ). Virulence characterization data of European field T. gondii strains are worryingly scarce ( Uzelac et al., 2020 ; Fernández-Escobar et al., 2021 ).…”
Section: Integrative Analysis: Evidence From a Pan-european Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…In short, findings should be always interpreted cautiously, as well as with interest, since strains that circulate in wildlife are a source of infection for domestic animals and humans, and have been associated with greater pathogenicity at least in North and South America ( Dubey et al., 2014 ). Virulence characterization data of European field T. gondii strains are worryingly scarce ( Uzelac et al., 2020 ; Fernández-Escobar et al., 2021 ).…”
Section: Integrative Analysis: Evidence From a Pan-european Perspectivementioning
confidence: 99%
“…The generation of WGS data on further strains including European type II strains could help to better understand the real genetic diversity within the dominant European strains, to explore the possible exchange of sequence blocks between clonal lineages in Europe and probably to link genetic differences not covered by the traditional widely used typing methods with phenotypic differences ( e.g. , virulence in mice) evidenced in literature between European isolates ( Fernández-Escobar et al., 2020b ; Fernández-Escobar et al., 2021 ).…”
Section: Integrative Analysis: Evidence From a Pan-european Perspectivementioning
confidence: 99%
“…Yet, this would imply that a number of the more virulent genotypes detected in SEE may persist along with the multitude of genotypes of low virulence. The findings of virulent genotypes in domestic animals in SEE along with the reports from Spain [23,62], where mouse virulent genotypes have also been isolated from pigs and sheep, call for vigilance as the impact of infection with more virulent genotypes may be underappreciated in Europe. Informed Consent Statement: Informed consent was obtained from all subjects involved in the study as outlined in the above Institute for Medical Research Ethics Committee Decision.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies concluded that the allelic combination of ROP18/ROP5 is highly predictive of virulence in mice across globally distributed T. gondii strains ( Dubey et al., 2014 ; Shwab et al., 2016 ). Nonetheless, there is growing evidence that this correlation is inconsistent for some genotypes ( Bernstein et al., 2021 ; Fernández-Escobar et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…There was an attempt to standardize the calculation of cumulative mortality rate by Saraf et al. (2017) , accepted as a consensus for virulence in mice assessment, but the fact is that this protocol has been applied in very few publications ( Costa Viegas de Lima et al., 2019 ; Fernández-Escobar et al., 2020 ; Uzelac et al., 2020 ; Fernández-Escobar et al., 2021 ). Current animal welfare policies, which strictly frame scientific research, aim to minimize the use of laboratory animals and to refine the experiments.…”
Section: Introductionmentioning
confidence: 99%